IMPACT OF HARD PROJECT MANAGEMENT AND TEAM MOTIVATION FOR PROJECT PERFORMANCE - U.L.T P. Gunasekare; S.H. Pramudika (Faculty of Economics, Universitas Sriwijaya, 2023)
This study focused on the impact of Hard Project Management Practices (HPMPs) and Team Motivation (TM) for successful Project Performance (PP). Further, it examines how TM mediates the link between HPMPs and PP. A qualitative data collection section sought to find challenges faced by the construction industry in Sri Lanka while exploring the association of HPMPs and PP further. Both public and private sector 131 construction projects were selected as the sample by way of the convenience sampling method. Semi-structured interviews were conducted with the managerial capacity officers. Accordingly, this research found that there is a slight impact of HPMPs on PP. But when it combines with TM the PP is boosted significantly. The mediator analysis proved that even though the construction projects have sound HPMPs, those will impair project performance if they would not consider team motivation properly. And, there are many other variables outside this model that are discussed under qualitative analysis, especially the factors/challenges which are unforeseen in the external environment.